2012
DOI: 10.1007/s12098-012-0817-6
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Factors for Persistent Asthma in Lucknow

Abstract: Since patients with persistent asthma are more likely to have uncontrolled asthma and since persistent asthma is associated with residence closer to heavy traffic and exposure to second hand smoke, minimizing exposures to these may help in better asthma control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Intense truck traffic was considered present when truck traffic was reported almost the whole day and this was consistent with other studies [28]. …”
Section: Methodssupporting
confidence: 88%
“…Intense truck traffic was considered present when truck traffic was reported almost the whole day and this was consistent with other studies [28]. …”
Section: Methodssupporting
confidence: 88%
“…[22] In this study, we found persistent asthma to be statistically significantly associated with previous use of bronchodilators and lower pulmonary function in comparison to intermittent asthma.…”
Section: Discussionmentioning
confidence: 49%
“…However, our recent original article reported statistically significant association between persistent asthma and uncontrolled asthma. [22] (b) Our objective was to assess the association of CRHR1 gene polymorphism with persistent asthma, not with the occurrence of asthma; therefore, we did not recruit healthy controls. Nonetheless, further case-control studies with a larger sample size and with long-term follow-up will undoubtedly strengthen the role of the CRHR1 gene polymorphism in childhood asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a significant repetition of G542X mutation had been observed among cases when compared with controls; nevertheless, only G551D was mainly related to asthma risk, but G542X showed no association with asthma. 1 Another interesting point in our work is the clear link between individuals with single W1282X mutation and the increased risk of recurrent chest infection and bronchiectasis; moreover, probands with double mutations (36 cases, 59%) were at increased risk for severe symptoms, earlier onset of symptoms, higher incidence of complications, and increased frequency of hospital admissions. This observation can be considered as specific pulmonary phenotype of CFTR-related disorders.…”
Section: Discussionmentioning
confidence: 71%
“…CFTR is a 230-kb gene located on chromosome 7 encoding a 1,480-amino acid polypeptide, which functions as a chloride channel in the epithelial membrane. 1 Bronchial asthma is a complex respiratory disorder characterized by marked heterogeneity in disease triggers and response to therapy. 2 The interaction of genetic, environmental, and host factors may contribute to the development of childhood asthma and defines its progress, including persistence and severity.…”
Section: Introductionmentioning
confidence: 99%